2010
DOI: 10.1167/iovs.10-5457
|View full text |Cite
|
Sign up to set email alerts
|

Human Optical Axial Length and Defocus

Abstract: Significant changes in optical axial length occurred in human subjects after 60 minutes of monocular defocus. The bidirectional optical axial length changes observed in response to defocus implied the human visual system is capable of detecting the presence and sign of defocus and altering optical axial length to move the retina toward the image plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
172
5
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(212 citation statements)
references
References 65 publications
28
172
5
2
Order By: Relevance
“…Similarly, some studies argue that increase in axial length decreases choroidal thickness while increased degree of myopia results in thinner choroid layer (20,21). In our study, we did not come across any significant correlation between average axial length and choroidal thickness.…”
Section: Methodscontrasting
confidence: 46%
See 1 more Smart Citation
“…Similarly, some studies argue that increase in axial length decreases choroidal thickness while increased degree of myopia results in thinner choroid layer (20,21). In our study, we did not come across any significant correlation between average axial length and choroidal thickness.…”
Section: Methodscontrasting
confidence: 46%
“…In addition to various structural changes in the retina, increase in axial length also leads to a decrease in retinal function (21). Similarly, some studies argue that increase in axial length decreases choroidal thickness while increased degree of myopia results in thinner choroid layer (20,21).…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been shown that additional manual analysis of the Lenstar A-scan data originating from the posterior eye can provide measurements of retinal thickness (RT, the distance from the inner limiting membrane to the retinal pigment epithelium) and ChT (the distance from the retinal pigment epithelium to posterior choroid). 4,7 This manual analysis in this study was performed by two independent masked observers. The estimates of ChT and RT from the two observers correlated closely (r 2 ¼ 0.94 and 0.99 for ChT and RT, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The development of precise optical techniques for the measurement of AXL has shown that a range of different physiological factors can lead to short-term changes in this biometric parameter. Changes in accommodation, [1][2][3] imposed defocus, 4 alterations in IOP 5,6 and water loading 7 have all been found to be associated with short term changes in human AXL. Significant diurnal variations in AXL have also been documented.…”
Section: Introductionmentioning
confidence: 99%
“…Swarbrick et al (2015) describe this apparent axial shortening as partially due to an established reduction in central corneal epithelial thickness in OK wear (Alharbi and Swarbrick 2003) and partially due to speculative choroidal thickening. (Read et al 2010) The older age of the paediatric group here is also most similar to Swarbrick et al (2015), where all other studies demonstrate younger baseline ages and faster myopia progression. It or stability.…”
Section: Axial Length Changes and Binocular Visionsupporting
confidence: 58%